2022
DOI: 10.1111/rsp3.12527
|View full text |Cite
|
Sign up to set email alerts
|

The resilience of Russian Arctic cities 1989–2017

Abstract: The topic of economic resilience is important and widely discussed today. However, the resilience of Russian regions and cities is insufficiently studied by indicator methods (without constructing an index). The paper aims to fill this gap, and is based on R. Martin's method: the resistance of each city was calculated and compared with all other cities. The method was tuned: instead of employment (partly unavailable) as a resilience indicator, we took population, which generally correlates with employment. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Similarly, Galtseva et al (2022) found that the creation of mono‐industrial characteristics in the northern economy of Russia was based on the production of gold. Polyachenko (2022) also suggested that different Russian cities are specialized in different industries such as oil, gas, mining, military, and nuclear production. Axenov et al (2020) and Pilyasov and Molodtsova (2022) highlighted the dominance of the big and biggest industrial enterprises in cities.…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%
“…Similarly, Galtseva et al (2022) found that the creation of mono‐industrial characteristics in the northern economy of Russia was based on the production of gold. Polyachenko (2022) also suggested that different Russian cities are specialized in different industries such as oil, gas, mining, military, and nuclear production. Axenov et al (2020) and Pilyasov and Molodtsova (2022) highlighted the dominance of the big and biggest industrial enterprises in cities.…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%